Ripensare la tolleranza religiosa in Utopia di Thomas More - Arrigo, Giacomo Maria (Filosofia Morale/Moral Philosophy, 2024)
This article revisits the idea of religious tolerance in Thomas More’s Utopia. By reviewing the often-conflicting readings that have been given to this concept, the article maps More’s influences on later Deism of 17th and 18th centuries, and shows that Utopia’s tolerance is based on the critique of the notion of pride, which is already the basis of Utopian communism. In arguing the impracticality of possessing truth because God is superior to reason (“supra mentis humanae captum”), More thus removes the possibility of exercising dominion in religious affairs.